Annual reproductive cycle of males of the flat-faced fruit-eating bat, Artibeus planirostris (Chiroptera: Phyllostomidae) - Beguelini, Mateus R. [UNESP]; Puga, Cintia C.I. [UNESP]; Taboga, Sebastião R. [UNESP]; Morielle-Versute, Eliana [UNESP] (Elsevier, 2013)
Artibeus planirostris is an endemic species of Phyllostomid bat from the Neotropical region. Some studies have indicated that it exhibits seasonal bimodal polyestry; however, others postulate that it may be able to produce young at any time during the year. Thus, the aim of this study was to evaluate the annual variations in testicular and epididymal parameters of this species in southeast Brazil and try to understand how the reproduction of this species is regulated in this environment. Sixty mature male specimens, collected between June 2009 and May 2010, were submitted to morphometric and immunohistochemical analysis. Our study showed that A. planirostris presented a continuously active pattern of spermatogenesis throughout the year, presenting spermatozoa inside its cauda epididymis in all months, but with two pronounced peaks of spermatogenic production, one in September and other in February. We propose that the males developed these two peaks in order to produce sufficient sperm for the reproduction in a harem system and to synchronize with the female reproductive cycle, which had a bimodal polyestric pattern. Control of this variation is directly linked to the expression of the androgen receptor (AR) in Sertoli cells and to serum testosterone levels, which appear to synchronize to establish these two peaks. In the months preceding the two peaks, the testis have a higher expression of the AR, which possibly stimulates the increase in PCNA, and drives a gradual increase in the testicular parameters. Taken together the results suggest that if sperm storage happens in this species, it is of short duration. © 2013 Elsevier Inc.
Keywords: Chiroptera; Phyllostomidae; Reproduction; Seasonality; androgen receptor; testosterone; animal cell; animal experiment; animal tissue; Artibeus planirostris; bat; body weight; Brazil; controlled study; day length; epididymis; female; gonad; high temperature; immunohistochemistry; low temperature; male; morphometrics; nonhuman; ovary cycle; priority journal; protein expression; reproduction; seasonal variation; Sertoli cell; sperm; spermatid; spermatocyte; spermatogenesis; spermatogonium; spermatozoon; summer; testis; testosterone blood level; winter; Animals; Epididymis; Female; Male; Organ Size; Receptors, Androgen; Seasons; Spermatogenesis; Testis